Sustainable Surfactin Production by Bacillus subtilis Using Crude Glycerol from Different Wastes - Tomasz Janek; Eduardo J. Gudiña; Xymena Połomska; Piotr Biniarz; Dominika Jama; Lígia R. Rodrigues; Waldemar Rymowicz; Zbigniew Lazar (Molecules, 2021)
Most biosurfactants are obtained using costly culture media and purification processes, which limits their wider industrial use. Sustainability of their production processes can be achieved, in part, by using cheap substrates found among agricultural and food wastes or byproducts. In the present study, crude glycerol, a raw material obtained from several industrial processes, was evaluated as a potential low-cost carbon source to reduce the costs of surfactin production by Bacillus subtilis #309. The culture medium containing soap-derived waste glycerol led to the best surfactin production, reaching about 2.8 g/L. To the best of our knowledge, this is the first report describing surfactin production by B. subtilis using stearin and soap wastes as carbon sources. A complete chemical characterization of surfactin analogs produced from the different waste glycerol samples was performed by liquid chromatography–mass spectrometry (LC-MS) and Fourier transform infrared spectroscopy (FTIR). Furthermore, the surfactin produced in the study exhibited good stability in a wide range of pH, salinity and temperatures, suggesting its potential for several applications in biotechnology.